Supervised Rehabilitation May Lead to Better Outcome than Home-Based Rehabilitation Up to 1 Year after Anterior Cruciate Ligament Reconstruction - Hye Chang Rhim; Jin Hyuck Lee; Seo Jun Lee; Jin Sung Jeon; Geun Kim; Kwang Yeol Lee; Ki-Mo Jang (Medicina, 2020)
Background and objectives: Previous studies consistently found no significant difference between supervised and home-based rehabilitation after anterior cruciate ligament reconstruction (ACLR). However, the function of the nonoperative knee, hamstring strength at deep flexion, and neuromuscular control have been overlooked. This prospective observational study was performed to investigate the outcomes after ACLR in operative and nonoperative knees between supervised and home-based rehabilitations. Materials and Methods: After surgery, instructional videos demonstrating the rehabilitation process and exercises were provided for the home-based rehabilitation group. The supervised rehabilitation group visited our sports medicine center and physical therapists followed up all patients during the entire duration of the study. Isokinetic muscle strength and neuromuscular control (acceleration time (AT) and overall stability index (OSI)) of both operative and nonoperative knees, as well as patient-reported knee function (Lysholm score), were measured and compared between the two groups 6 months and 1 year postoperatively. Results: The supervised rehabilitation group showed higher muscle strength of hamstring and quadriceps in nonoperative knees at 6 months (hamstring, p = 0.033; quadriceps, p = 0.045) and higher hamstring strength in operative and nonoperative knees at 1 year (operative knees, p = 0.035; nonoperative knees, p = 0.010) than the home-based rehabilitation group. At 6 months and 1 year, OSIs in operative and nonoperative knees were significantly better in the supervised rehabilitation group than in the home-based rehabilitation group (operative knees, p < 0.001, p < 0.001; nonoperative knees, p < 0.001, p < 0.001, at 6 months and 1 year, respectively). At 1 year, the supervised rehabilitation group also demonstrated faster AT of the hamstrings (operative knees, p = 0.016; nonoperative knees, p = 0.036). Lysholm scores gradually improved in both groups over 1 year; however, the supervised rehabilitation group showed higher scores at 1 year (87.3 ± 5.8 vs. 75.6 ± 15.1, p = 0.016). Conclusions: This study demonstrated that supervised rehabilitation may offer additional benefits in improving muscle strength, neuromuscular control, and patient-reported knee function compared with home-based rehabilitation up to 1 year after ACLR.